Use of oral health care services in Finnish adults - results from the cross-sectional Health 2000 and 2011 Surveys - Anna L. Suominen; Sari Helminen; Satu Lahti; Miira M. Vehkalahti; Matti Knuuttila; Sinikka Varsio; Anne Nordblad (BMC, 2017)
Abstract Background During the 2000s, two major legislative reforms concerning oral health care have been implemented in Finland. One entitled the whole population to subsidized care and the other regulated the timeframes of access to care. Our aim was, in a cross-sectional setting, to assess changes in and determinants of use of oral health care services before the first reform in 2000 and after both reforms in 2011. Methods The data were part of the nationally representative Health 2000 and 2011 Surveys of adults aged ≥ 30 years and were gathered by interviews and questionnaires. The outcome was the use of oral health care services during the previous year. Determinants of use among the dentate were grouped according to Andersen's model: predisposing (sex, age group), enabling (education, recall, dental fear, habitual use of services, household income, barriers of access to care), and need (perceived need, self-rated oral health, denture status). Chi square tests and logistic regression analyses were used for statistical evaluation. Results No major changes or only a minor increase in overall use of oral health care services was seen between the study years. An exception were those belonging to oldest age group who clearly increased their use of services. Also, a significant increase in visiting a public sector dentist was observed, particularly in the age groups that became entitled to subsidized care in 2000. In the private sector, use of services decreased in younger age groups. Determinants for visiting a dentist, regardless of the service sector, remained relatively stable. Being a regular dental visitor was the most significant determinant for having visited a dentist during the previous year. Enabling factors, both organizational and individual, were emphasized. They seemed to enable service utilization particularly in the private sector. Conclusions Overall changes in the use of oral health care services were relatively small, but in line with the goals set for the reform. Older persons increased use of services in both sectors, implying growing need. Differences between public and private sectors persisted, and recall, costs of care and socioeconomic factors steered choices between the sectors, sustaining inequity in access to care.